Treadmill Exercise Ameliorates Short-Term Memory Disturbance in Scopolamine-Induced Amnesia Rats - Heo, Yu-Mi (Korean Continence Society, 2014)
PURPOSE: Scopolamine is a nonselective muscarinic cholinergic receptor antagonist, which induces impairment of learning ability and memory function. Exercise is known to ameliorate brain disturbance induced by brain injuries. In the present study, we investigated the effect of treadmill exercise on short-term memory in relation to acetylcholinesterase (AChE) expression in the hippocampus, using a scopolamine-induced amnesia model in mice. METHODS: To induce amnesia, 1 mg/kg scopolamine hydrobromide was administered intraperitoneally once per day for 14 days. A step-down avoidance test for short-term memory was conducted. AChE histochemistry, immunohistochemistry for collagen IV, and doublecortin were performed. RESULTS: Short-term memory deteriorated in the mice with scopolamine-induced amnesia, concomitant with enhanced AChE expression and suppression of angiogenesis in the hippocampus. Critically, treadmill exercise ameliorated short-term memory impairment, suppressed AChE expression, and enhanced angiogenesis in the mice with scopolamine-induced amnesia. CONCLUSIONS: Overexpression of AChE is implicated in both brain and renal disease. The findings of our study indicate that treadmill exercise may be of therapeutic value in neurodegenerative and renal diseases by suppressing the effects of AChE expression.